2021
DOI: 10.1016/j.mayocp.2021.07.003
|View full text |Cite
|
Sign up to set email alerts
|

The High Stakes of Outsourcing in Health Care

Abstract: Outsourcing in health care has become increasingly common as health system administrators seek to enhance profitability and efficiency while maintaining clinical excellence. When clinical services are outsourced, however, the outsourcing organization relinquishes control over its most important service value: high-quality patient care. Farming out work to an external service provider can have many unintended results, including inconsistencies in standards of care; harmful medical errors; declines in patient an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 46 publications
(47 reference statements)
2
3
0
Order By: Relevance
“…The present study's findings also showed that the dominant model had been service purchasing, as 84% of total outsourced services have been finalized using this model. This part of the findings is consistent with the results of some studies (32,33). One of the reasons attributed to the high usage of this model is that this model has been used for a long time, and as a result, managers are familiar with the terms and conditions of this type model.…”
Section: Discussionsupporting
confidence: 91%
“…The present study's findings also showed that the dominant model had been service purchasing, as 84% of total outsourced services have been finalized using this model. This part of the findings is consistent with the results of some studies (32,33). One of the reasons attributed to the high usage of this model is that this model has been used for a long time, and as a result, managers are familiar with the terms and conditions of this type model.…”
Section: Discussionsupporting
confidence: 91%
“…Findings the present study also represent that the dominant model has been service purchasing as 84% of total outsourced services have been nalized using this model. This part of ndings is consistent with the results of some studies (Berry et al, 2021;Malovec et al, 2015) .one of the reasons attributed to the high usage of this model is that this model has been using for long time ago and as a result familiarity of managers with the terms and conditions of this type model. Additionally, simplicity in implementation has paved the way for being institutionalized.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, addressing the high stakes associated with outsourcing in health care highlighted the importance of carefully sourcing services for public health services as they do not necessarily result in cost reduction [ 30 ]. Effective outsourcing requires a significant oversight of the overall performance of the outsourced services.…”
Section: Discussionmentioning
confidence: 99%
“…Effective outsourcing requires a significant oversight of the overall performance of the outsourced services. Detailed contracts between the outsourced services and the contractor should include indicators of clinical quality, business efficiency, patient satisfaction and professionalism [ 30 ].…”
Section: Discussionmentioning
confidence: 99%